Effect of acupuncture on insomnia following stroke: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Cao, Yan; Yin, Xuan; Soto-Aguilar, Francisca; Liu, Yiping; Yin, Ping; Wu, Junyi; Zhu, Bochang; Li, Wentao; Lao, Lixing; Xu, Shifen
Abstract Background The incidence, mortality, and prevalence of stroke are high in China. Stroke is commonly associated with insomnia; both insomnia and stroke have been effectively treated with acupuncture for a long time. The aim of this proposed trial is to assess the therapeutic effect of acupuncture on insomnia following stroke. Methods This proposed study is a single-center, single-blinded (patient-assessor-blinded), parallel-group randomized controlled trial. We will randomly assign 60 participants with insomnia following stroke into two groups in a 1:1 ratio. The intervention group will undergo traditional acupuncture that achieves theDe-qi sensation, and the control group will receive sham acupuncture without needle insertion. The same acupoints (DU20, DU24, EX-HN3, EX-HN22, HT7, and SP6) will be used in both groups. Treatments will be given to all participants three times a week for the subsequent 4 weeks. The primary outcome will be the Pittsburgh Sleep Quality Index. The secondary outcomes will be: the Insomnia Severity Index; sleep efficacy, sleep awakenings, and total sleep time recorded via actigraphy; the National Institutes of Health Stroke Scale; the Stroke-Specific Quality of Life score; the Hospital Anxiety and Depression Scale. The use of estazolam will be permitted and regulated under certain conditions. Outcomes will be assessed at baseline, 2 weeks after treatment commencement, 4 weeks after treatment commencement, and at the 8-week follow-up. Discussion This proposed study will contribute to expanding knowledge about acupuncture treatment for insomnia following stroke. This will be a high-quality randomized controlled trial with strict methodology and few design deficits. It will investigate the effectiveness of acupuncture as an alternative treatment for insomnia following stroke. Trial registration Chinese Clinical Trial Registry identifier:ChiCTR-IIC-16008382 . Registered on 28 April 2016.